A Study On The Perfomance Of Sedimentation Tank At The Sungai Kampar Water Treatmeny Plant. - Adlan, Ir Dr Mohd Nordin; Abd Aziz, Assoc. Prof. Dr Hamidi; Mohd Isa, Ir Mohd Yusuf; Zainal Abidin, Abd Razak; Hasan, Rahmat (2000)

(untitled)
This paper discusses the performance of soIid-liquid separation pfocess at the Sg Kampar Water Treatment works.